The Efforts to Improve Lecturer Performance through Professional Commitment and Motivation Based on Spiritual Values - Muslikh; Simon, Zainal Zawir (Research of Business and Management, 2023)
This study examined the effect of professional commitment and spirituality-based motivation on lecturer performance. The survey method was carried out by distributing questionnaires to 50 lecturers of YARSI University. The results showed that spirituality-based motivation had a positive and significant effect on professional commitment, spirituality-based motivation had a positive and significant effect on lecturer performance, and professional commitment had a positive and significant effect. Professional commitment mediates spirituality-based motivation on the performance of lecturers at YARSI University. The implications of this research are to develop professionalism in a sustainable manner by carrying out reflective and communication actions to develop the profession and apply it in the teaching and learning process as a form of good performance or self-performance. This research contributes to improving the performance of lecturers who are relevant to their respective fields so that students can obtain additional knowledge and skills to improve the quality of their education